Legal Protection of Famous Trademarks Under the Principle of Good Faith From a Legal Perspective in Indonesia - Achmad Arrizal; Tasya Aura Octaviany; Sonia Fitri Anggrayani; Dudung Hidayat; Raden Handiriono (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the age of globalization, prominent brands play a crucial role in shaping customer identity and trust while enhancing product competitiveness in the global market. This paper examines the legal safeguarding of renowned trademarks in Indonesia, grounded in the principle of good faith as outlined in Law Number 20 of 2016 about Trademarks and Geographical Indications. This study employs normative juridical research methodologies to examine the preventative and repressive legal protection of renowned trademarks, alongside the implementation of the concept of good faith in trademark registration and utilization. The results show that although regulations have adopted protections for well-known brands, their implementation still faces various challenges, such as weak oversight and lack of legal certainty, which have the potential to harm rights holders and consumers. Therefore, to create effective and fair brand protection, the legal system must be strengthened by establishing a database of well-known brands, accelerating legal processes, educating the public, and collaborating across sectors.